2018
DOI: 10.1186/s12935-018-0548-5
|View full text |Cite
|
Sign up to set email alerts
|

A cross-talk between integrin β4 and epidermal growth factor receptor induces gefitinib chemoresistance to gastric cancer

Abstract: BackgroundGastric cancer presents a major health burden worldwide. Therefore, many molecular targeting agents have been evaluated for treatment of gastric cancer. Gefitinib has shown anticancer activity against gastric cancer which work through inhibiting epidermal growth factor receptor (EGFR). However, the effect of gefitinib is limited due to its resistance. Therefore, understanding the mechanisms of gefitinib resistance is desperately needed to formulate novel strategies against gastric cancer. Here, we an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…This effect was verified by Western blot analysis ( Figure 7 b). Integrin β 4 (ITGB4) is unable to bind to COL1 but has been described to mediate cell-cell-contacts as a hemidesmosome and to induce an active crosstalk with growth factor receptors, e.g., EGFR [ 48 , 49 ]. Concerning the upregulated pEGFR levels in MDA-MB-231kd cells shown in Figure 1 , we therefore explicitly checked for pEGFR in both cell lines by Western blot ( Figure 7 c).…”
Section: Resultsmentioning
confidence: 99%
“…This effect was verified by Western blot analysis ( Figure 7 b). Integrin β 4 (ITGB4) is unable to bind to COL1 but has been described to mediate cell-cell-contacts as a hemidesmosome and to induce an active crosstalk with growth factor receptors, e.g., EGFR [ 48 , 49 ]. Concerning the upregulated pEGFR levels in MDA-MB-231kd cells shown in Figure 1 , we therefore explicitly checked for pEGFR in both cell lines by Western blot ( Figure 7 c).…”
Section: Resultsmentioning
confidence: 99%
“…Gefitinib-mediated cell toxicity was substantially reduced when hepatocarcinoma cells were exposed to laminin-332 but not to other ECM proteins such as collagen or fibronectin [27]. More recently, high β4 integrin expression was associated with a gefitinib-resistant phenotype in gastric cancer cells [26]. The resistant phenotype could be reverted by RNA-mediated β4 silencing, whereas sensitive cells became more resistant to gefitinib after β4 overexpression.…”
Section: α6β4 Integrinsmentioning
confidence: 99%
“…A clinical study in 38 patients has indicated some correlation between β4 expression and gefitinib resistance. However, given the small sample size, it is far too early to draw any conclusion about the potential repercussions of this observation [26]. Another clinical study showed that β4 integrin polymorphism expression was associated with resistance to therapy.…”
Section: α6β4 Integrinsmentioning
confidence: 99%
“…For instance, ECM-mediated integrin β1 promotes liver metastasis of gastrointestinal cancer through focal adhesion kinase (FAK)-yes-associated protein 1 (YAP1)/tafazzin (TAZ) signaling, which is enhanced by vasodilator-stimulated phosphoprotein (VASP) [116]. In addition, ECM1-mediated integrin β4 promotes EMT and glucose metabolism via SOX2/HIF-1α signaling in gastric cancer [117] and modulates epidermal growth factor receptor (EGFR) signaling to induce gefitinib chemoresistance [118]. In pancreatic cancer, solute carrier family 39 member 4 (ZIP4) induces ZEB1 expression via STAT3 signaling and subsequently activate integrin α3β1 to regulate the JNK signaling pathway, leading to inhibit chemosensitivity by decrease gemcitabine transporter ENT1 [119].…”
Section: Integrinsmentioning
confidence: 99%
“…Taken together, the data support the critical roles of cancer cell adhesion molecules in tumor growth, metastasis, and chemoresistance ( Table 2). L-selectin Metastasis [113] Liver cancer E-selectin Tumor growth, Angiogenesis [111] Integrins Gastric cancer integrin β4 SOX2/HIF-1α signaling, EGFR EMT, Glucose metabolism, gefitinib chemoresistance [117,118] integrin β1 CXCL1, FAK/Akt signaling, MMP2/9 Adhesion, Metastasis [121] Pancreatic cancer integrin α3β1 ZIP4, ZEB1, STAT3 signaling, JNK signaling pathway Chemoresistance [119] Integrin family galectin-3, IL-8, NF-κB signaling Promote tumor growth, Metastasis [125] Colorectal cancer integrin α2β1 CDH17, FAK and Ras pathways Proliferation, Metastasis [120] integrin β1 TLR4, PI3K/Akt pathway Adhesion, Metastasis [123] Liver cancer integrin β3 IL-8, PI3K/Akt pathway Invasion [122] integrin αvβ3 galectin-1, FAK/PI3K/Akt signaling EMT, Sorafenib resistance [124] 3.4. Programmed Death-Ligand 1…”
Section: Integrinsmentioning
confidence: 99%